Analisis Disiplin dan Kinerja Karyawan pada Nippon Paint Bandung - Robi Al Ansyori; Ricki Ramadhan (JUDICIOUS, 2021)
In facing today's tight trade competition, companies are required to be able to compete with competitors in increasing company productivity in all fields. One of them is to improve employee discipline and performance, because the achievement of a company begins with employee discipline in carrying out their duties. This research was conducted at Nippon Paint Bandung, to find out how the application of discipline was carried out in improving the company's performance and productivity. This study uses a qualitative analysis method on the research output, it is found that Nippon Paint Bandung has applied progressive discipline, corrective discipline, and preventive discipline.